The Effects of Conditioned Medium Derived from Mesenchymal Stem Cells Cocultured with Hepatocytes on Damaged Hepatocytes and Acute Liver Failure in Rats - Li Chen; Jiexin Zhang; Lu Yang; Guoying Zhang; Yingjie Wang; Shichang Zhang (Hindawi Limited, 2018)
Mesenchymal stem cells (MSCs) and hepatocytes are two attractive sources of cell-based therapies for acute liver failure (ALF). The cotransplantation of hepatocytes with MSCs can improve the therapeutic performance for the treatment of ALF. However, the therapeutic potential of conditioned medium (CM) derived from MSCs cocultured with hepatocytes (MSC-H-CM) remains unclear. The purpose of this study was to investigate the effects of MSC-H-CM on damaged hepatocytes in vitro and on D-galactosamine-induced ALF in vivo. D-Galactosamine-treated L02 cells cultured in MSC-H-CM exhibited higher of cell viability and total protein synthesis than L02 cells cultured in MSC-CM, CM derived from hepatocytes (H-CM), MSC-CM + H-CM, or with nonconditioned medium (NCM). Lactate dehydrogenase and aspartate aminotransferase levels were lower in the supernatant of damaged L02 cells cultured in MSC-H-CM than in that of L02 cells cultured in other types of CM. The lowest percentage of apoptotic cells was observed after the MSC-H-CM treatment. When CM was injected into the tail vein of rats with ALF, MSC-H-CM was the most successful at preventing the release of liver injury biomarkers and in promoting the recovery of liver structure. The greatest survival rate 7 days after the first treatment was observed in the MSC-H-CM-treated rats. Our results reveal that the delivery of MSC-H-CM could be a novel strategy for integrating the therapeutic potentials of hepatocytes and MSCs for the treatment of ALF.